Bebbington, A., Abdulai, A.-G., Bebbington, D. H., Hinfelaar, M., & Sanborn, C. (2019). Gobernanza de las industrias extractivas: política, historia, ideas. Lima: Universidad del Pacífico. - Paredes, Maritza (2020)
Review of Gobernanza de las industrias extractivas: política, historia, ideas